Migrant, multicultural and diasporic heritage : beyond and between borders - Dellios, Alexandra; Henrich, Eureka (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Migrant, Multicultural and Diasporic Heritage explores the role heritage has played in representing, contesting and negotiating the history and politics of ethnic, migrant, multicultural, diasporic or 'other' heritages' in, within, between and beyond nations and national boundaries. Containing contributions from academics and professionals working across a range of fields, this volume contends that, in the face of various global 'crises', the role of heritage is especially important: it is a stage for the negotiation of shifting identities and for the rewriting of traditions and historical narratives of belonging and becoming. As a whole, the book connects and further develops methodological and theoretical discourses that can fuel and inform practice and social outcomes. It also examines the unique opportunities, challenges and limitations that various actors encounter in their efforts to preserve, identify, assess, manage, interpret and promote heritage pertaining to the experience and history of migration and migrant groups. Bringing together diverse case studies of migration and migrants in cultural heritage practice, Migrant, Multicultural and Diasporic Heritage will be of great interest to academics and students engaged in the study of heritage and museums, as well as those working in the fields of memory studies, public history, anthropology, archaeology, tourism and cultural studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Emigration and immigration -- History; Emigration and immigration -- Political aspects; Refugees -- History; Multiculturalism -- History; SOCIAL SCIENCE / Emigration & Immigration